Asking for Facebook Logins: An Egoist Case for Privacy - Drake, John R. (Journal of business ethics, 2016)
With the advent of social networking websites, privacy concerns have reached a new high. One particularly problematic concern entails employers requesting login credentials to popular social media platforms. While many people may consider this request unethical, they may not agree on the reasons it is unethical. One reason may be to blame the behavior on egoism. Egoism, however, comes in multiple flavors, not all of which would agree that violating privacy is acceptable. In this paper, we articulate how one egoist perspective provides a defense of privacy in the face of unjust information access requests. Objectivism, the philosophy of Ayn Rand, offers an egoist approach to ethics that values individual privacy on rational, self-interested grounds. By applying Objectivist principles to a business context, we observe that businesspeople should not violate other people’s privacy for short-term gains. Furthermore, we observe that privacy can be protected without distinct right to privacy. Rather, Objectivism’s conception of rational self-interest suggests that long-term flourishing is the proper end of individuals and businesses, predicated on, among other things, respecting privacy and enforcing individual rights.